Clinical utility of endomyocardial biopsies in the diagnosis of arrhythmogenic right ventricular cardiomyopathy in children. (October 2018) - Sreetharan, Shayenthiran; MacIntyre, Ciorsti; Fatah, Meena; Warren, Andrew; Wilson, Gregory; Hamilton, Robert
Abstract Background Histomorphometry of endomyocardial biopsies is one component of arrhythmogenic right ventricular cardiomyopathy (ARVC) diagnosis, although there is a need for stricter diagnostic criteria for this disease in pediatrics. The clinical utility of biopsy analysis as a component of ARVC diagnosis was evaluated in pediatric patients. Methods Histomorphometric analysis of fibrofatty infiltrate was completed on pediatric right ventricular endomyocardial biopsy samples. Myocardial replacement by fat and fibrosis was quantified. ARVC diagnosis was established using the 2010 ARVC Task Force criteria, with the biopsy measures compared across various ARVC diagnoses (definite, borderline, possible, or no ARVC). Receiver-operating characteristic (ROC) curve analysis was also completed using biopsy measures. Results The greatest proportion of fat, fibrosis, and myocardial replacement was in the definite ARVC cohort, and was significantly larger than for the other diagnosis cohorts. ROC curve analysis (with the biopsy analysis removed from the diagnostic classification) produced cutoff values of 15 and 25% myocardial replacement, which is lower than current adult diagnosis criteria. Conclusion We propose modifications in pediatric major and minor biopsy diagnosis criteria to allow for improved sensitivity. This study suggests that biopsy analysis in children is most significant for subjects with a more severe disease presentation.